Manajemen Kurikulum Dan Pembelajaran Bahasa Indonesia Di SDIT Muhammadiyah Al Kautsar Kartasura Tahun Pelajaran 2013/2014 - JUMININGSIH, Juminingsih; , Prof. Dr. Sutama, M.Pd (2015)
This thesis was written aims to determine: Curriculum Development and learning Indonesian, Curriculum Implementation in learning Indonesian and Curriculum Evaluation in learning Indonesian in SDIT Muhammadiyah Al Kautsar Kartasura. This study is a qualitative research. The research approach used in this study is a case study of data collection techniques used in this study are in-depth interviews (in- depht interviews), observation (observation), and documentation. The analysis technique used in this research is the analysis of an interactive model with triangulation in testing the credibility. Curriculum development in SDIT Muhammadiyah Al Kautsar Kartasura implemented by the national curriculum, in this case is the Department of Education Kemdikbud (Ministry of Education and Culture) then arranged in a systematic and organized with attention to the foundation and cornerstone of sociological, philosophical and psychological. In developing the curriculum SDIT Muhammadiyah Al Kautsar Kartasura have considered the principles or existing curriculum development theory. These principles are general principles and specific principles. The general principles include flexibility, continuity, effectiveness, and practical. Specific principles with regard to arranging goals, learning experiences, content and assessment. Learning Curriculum Implementation in Indonesian in SDIT Muhammadiyah Al Kautsar is the character education learning using learning model that is interesting and fun , which can increase the value of the character of students. Character development curriculum that is implemented into the learning activities, extra-curricular activities of students, the flagship program of the school, nursery Competition and activities of daily student. Curriculum evaluation to determine the effectiveness of the curriculum implemented in SDIT Muhammadiyah Al Kautsar in an effort to improve and enhance the curriculum. Aspects of curriculum evaluation in SDIT Muhammadiyah Al Kawthar is appropriate stages of curriculum development stage is the determination of objectives, planning, testing, field testing, implementation and quality control.